Perinatal mortality and its causes in a rural block in Tamil Nadu, Southern India: A community-based nonconcurrent cohort study - Anne George Cherian; Cherryl Tryphena; Kuryan George; Vinod Joseph Abraham; Venkata Raghava Mohan; Jasmine Helan Prasad (Wolters Kluwer Medknow Publications, 2022)
Background: Globally, over 130 million babies are born every year, and almost 8 million die before their first birthday. Data on perinatal mortality (PM) and its various causes are lacking in many parts of the world including India. Objectives: This study aimed to estimate stillbirth (SB), early neonatal, and PM rates and its causes over the last decade in a rural development block, India. Materials and Methods: This is a nonconcurrent cohort study, analyzing the births, SBs, and early neonatal deaths between January 2008 and December 2017. The World Health Organization-PM classification was used to allocate causes of death as well as maternal risk factors. Birth weights were classified using standard growth charts. Results: There were 20,704 births after 28 weeks gestation and where the fetus weighed more than 1000 g of which 285 were SBs. There were 20,419 live births with 229 early neonatal deaths. There was a significant decline in PM rate from 32 per 1000 to 11 per 1000. There was a decrease in the small for gestational age fetuses from 20% to 12.5%. The main cause for SBs was antepartum hypoxia (34.4%) and fetal growth disorders (26.3%). Complications of intrapartum events contributed to 32.8% of the early neonatal deaths. Conclusion: Steady decline in PM rate and in the number of small for gestational age fetuses over 10 years was seen. Pregnancy registration and follow-up help in giving us a better understanding of the causes of PM.